Development of evaluation model to improve green supply chain management by applying DEMATEL technique - Falatoonitoosi, Elham (2013)
Green supply chain management (GSCM) has become a practical approach to develop environmental performance. Under strict regulations and stakeholder pressures, enterprises need to enhance and improve GSCM practice, which are influenced by both traditional and green factors. The aim of the study was to develop a framework to improve green supplier selection by considering on green supplier selection. Indeed the essential gap in previous studies was lack of formal models to help improving green supplier management especially green supplier selection development. Also in many studies, there was not any consideration to complex causal relationship between criteria of the system consists of dependences and feedbacks among criteria and alternatives simultaneously. Consequently, a finding of this study is an evaluation framework to select the most eligible green suppliers by examining the influential and important factors among twenty-one elements of five main GSCM practices, namely Green Logistics, Organizational Performance, Green Organizational Activities, Environmental Protection and Green Supplier Evaluation. In fact, this model enables enterprises to figure out the main aspects for evaluating green suppliers and indicates that which one of these aspects are more important or have more impact to other aspects. Another finding of the study is related to the results of the calculations that assist automotive companies by two ways. First, company tends to select new suppliers or organize their suppliers according to the green image for being successful in today competitive market. Results show which factors are more effective and important for being green as a suppliers. Second, the results of proposed model enables manufacturers who are supplier for other companies to became a green supplier and produce based on green practices. The nature of supplier selection is a complex multi-criteria problem including both quantitative and qualitative factors, which may be in conflict and may be uncertain. So, Multi Criteria Decision Making (MCDM) methods are required to handle and solve the problem effectively. Consequently, decision-making trial and evaluation laboratory technique (DEMATEL) has been applied in this study to obtain direct and indirect influences between criteria and calculate the causal relationships and strength among criteria. By this way, structural relationship between system elements is better understood and finding ways to solve complicate system problems is possible. Consequently, all factors have been divided into cause and effect groups and elements are ranked based on the most important and most influential aspects. Factors that belong to the cause group have significant impact on factors of effect group. It means that if the factors in cause group improve, the factors of effect group will be improved automatically and it cause to have reduction waste on time, energy and resources.